2002
DOI: 10.1210/en.2002-220522
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Testosterone-Regulated Prominin-Like Gene in the Rat Ventral Prostate

Abstract: More than two dozen androgen-responsive genes were identified from the castrated rat ventral prostate on the basis of their induction by exogenous testosterone. One of the identified genes encodes a novel 886-amino-acid protein that was named prominin-like protein 2 (PROML2) because it shares 32% identity to prominin and prominin-like protein 1, a family of important plasma membrane proteins with five transmembrane domains. The rat PROML2 gene is expressed abundantly in the glandular epithelial cells of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Consistently, among the prostatic carcinoma cells of human origin commonly studied, e.g. DU145, PC3 and LNCaP, only the latter showed good expression of Prominin-2 as assessed by PCR (Zhang et al 2002). Inasmuch as these prostate cancer cells predominantly display more luminal, secretory-like phenotypes this might indicate that the diVerentiation grade of the prostate tumors could negatively correlate with PROMININ-2 expression.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Consistently, among the prostatic carcinoma cells of human origin commonly studied, e.g. DU145, PC3 and LNCaP, only the latter showed good expression of Prominin-2 as assessed by PCR (Zhang et al 2002). Inasmuch as these prostate cancer cells predominantly display more luminal, secretory-like phenotypes this might indicate that the diVerentiation grade of the prostate tumors could negatively correlate with PROMININ-2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…DiVerential gene expression studies revealed that a number of basal cell markers were expressed as well by cancer cells especially by those that were poorly diVerentiated (McDonnell et al 1992;Liu et al 1996). Expression of Prominin-2, however, was hardly detectable by northern blot in prostate cancer cells (Zhang et al 2002). Consistently, among the prostatic carcinoma cells of human origin commonly studied, e.g.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations